A comparative analysis of stem cells derived from young rabbit knee joints: the potentially superior performance of decellularized extracellular matrix pretreated infrapatellar fat pad stem cells on nanofiber scaffolds - Wei, Zhixin; Yu, Qingqing; Xie, Qingyun; Liao, Dongfa; Gou, Xue; Chen, Song (Frontiers in Cell and Developmental Biology, 2025)
IntroductionOsteoarthritis (OA) remains a significant clinical challenge, necessitating improved strategies for cartilage repair. Stem cells and scaffolds have crucial roles in tissue repair and regeneration. In this study, we comprehensively investigated the proliferation and differentiation potential of infrapatellar fat pad stem cells (IFPSCs), synovium-derived stem cells (SDSCs), and bone marrow stem cells (BMSCs) from unpretreated knee joints in young rabbits, and after decellularized extracellular matrix (dECM) deposition by stem cell pretreatment in vitro.MethodsWe also examined adhesion and differentiation effects of poly-L-lactic acid (PLLA) and poly-D, L-lactic acid (PDLLA) scaffolds after inoculation with the three stem cell types. We conducted osteogenic, adipogenic, and chondrogenic induction studies using three unpretreated stem cell groups, nine stem cell groups cross-preconditioned with different dECM types, and six stem cell groups cultured on nanofiber PLLA and PDLLA scaffolds. Staining and PCR analyses were then performed.ResultsIn vitro studies indicated that without pretreatment, IFPSCs exhibited the highest proliferation capacity, followed by SDSCs, while BMSCs had the lowest proliferation rate. After cross-pretreatment with dECMs from different sources, IFPSCs pretreated with IECM (decellularized extracellular matrix deposited by IFPSCs) showed the greatest proliferation. BMSCs displayed the highest osteogenic potential, while SDSCs and IFPSCs showed greater chondrogenic potential. No significant differences were observed in adipogenic potential among the three groups. BMSCs exhibited reduced osteogenic potential after pretreatment with all three dECMs, whereas IFPSCs and SDSCs showed enhanced osteogenic potential following SECM and IECM pretreatment, respectively. Additionally, all 3 cell types showed reduced lipogenic potential after pretreatment with the three dECM types. For chondrogenesis, BECM pretreatment were suitable for enhancing the chondrogenic potential of all 3 cell types. Furthermore, BMSCs and IFPSCs exhibited better adhesion and survival than SDSCs on electrospun scaffolds, which mimicked dECM structures. Besides, BMSCs and IFPSCs are more suitable for PLLA to promote osteogenic, adipogenic, and chondrogenic differentiation, whereas SDSCs are better suited for PDLLA.DiscussionOverall, it is anticipated that IFPSCs can be expanded with BECM pretreatment in vitro, and when combined with degradable nanofiber PLLA scaffolds in vivo, will facilitate better OA repair.